Microdiscectomy and Minimally Invasive Discectomy Using a Tubular Retractor System for Lumbar Disc Herniation: A Comparative Study - Keerthan Ranga Nayak U; Shyamasunder N. Bhat; Nishanth Ampar; Raghuraj S. Kundangar (Gazi Medical Journal)
Objective: The findings of clinical research comparing microdiscectomy and a minimally invasive approach are ambiguous or inconsistent. Therefore, we compared the two interventions in terms of their clinical, radiological, and functional outcomes for lumbar disc herniation. Methods: Seventy-eight patients who underwent microdiscectomy and minimally invasive discectomy (MID) using tubular retractors at a single level were prospectively followed up. The visual analogue scale (VAS) was used to assess the intensity of radicular pain. Clinical evaluation involved the straight leg raising test and the assessment of motor and sensory functions. We used the Oswestry Disability Index to assess functional outcomes. Instability was assessed by measuring the angular rotation and sagittal translation in dynamic lateral radiographs. The approaches were compared in terms of the length of incision, surgical duration, blood loss, length of hospitalization, and complications. Results: The most commonly herniated disc was L4-L5. VAS significantly (p=0.0001) improved with MID using tubular retractors than with microdiscectomy in one month. The incision length required was significantly (p=0.05) smaller and the intraoperative blood loss was lesser for MID than for microdiscectomy. There was no spinal instability in either group at the end of the final follow-up. Although there was no significant difference in the clinical outcome, the functional outcome improved in both groups at the 1-year follow-up, and the incidence of postoperative complications was similar between the groups. Conclusion: Microdiscectomy and MID are comparable procedures with comparable results, with a tendency for higher intraoperative complications in MID.